“Determinación de proteínas totales y albúmina como aporte para el establecimiento de valores de referencia en estudiantes de unidades educativas rurales del catón Riobamba” - Rubio Duche, Karen Leonela (2018)
The reference assessment provides important information about the patient’s nutrition status and it is also an indicator of the presence of diseases. The objective of this work was to determine the proteins and albumin as a contribution for the establishment of reference values in blood serum by means of biochemical analysis, in which we used the descriptive, field, cross-sectional type and qualitative-quantitative character by means of the survey application and biochemical tests automated equipment Dimension RxL Max found alterations in minor percentages known as hyperproteinemias and a lower degree of malnutrion was established. All this was supported by anthropometric measurements that are closely related, and thus to know the state of health of said population. Total protein and albumin values were determined in 14 – 18 years old students of the rural educational units of the Riobamba Canton, which were randomly selected, through a descriptive study. Currently, in the major of Clinical and Histopathological Laboratory of the National University of Chimborazo a research project is carried out. To this end, 12 educational units of the 30 programmed were studied, which were submitted to the definitive study, to reach the proposed objectives, venous blood samples were taken in order to process blood serum and analyze the different tests, being a total population of 163 students of which 52% were women and in 48% of men this research helped with important data within the assessment used for total protein 6.4 – 8.2 g/dl with 78% and albumin 3.4 – 5.0 g/dl.